Some Geometric Properties of Sequence Spaces Involving Lacunary Sequence. (9th January 2008) - Karakaya, Vatan
Abstract : We introduce new sequence space involving lacunary sequence connected with Cesaro sequence space and examine some geometric properties of this space equipped with Luxemburg norm.